Detection of the Vandibular Canal and the Mental Foramen in Panoramic Radiographs: Intraexaminer Agreement - Shibli, Jamil A.; Martins, Marilia C.; Loffredo, Leonor C. M. [UNESP]; Scaf, Gulnara [UNESP] (Allen Press Inc, 2012)
The aim of this study was to evaluate the intraexaminer agreement in the detection of the mandibular canal roof (MCR) and mental foramen (MF) in panoramic radiographs. Forty panoramic radiographs of edentulous patients were used. Two calibrated examiners (A and B) read the images 2 times, for both sides independently, under blind conditions. The interval between the readings was 10 days. The intraexaminer agreement in the interpretation of MCR and MF was performed by kappa statistics with linear weighting (x). The intraexaminer agreement for the detection of MCR, in the left side, was good for both examiners (A: kappa = 0.67; B: kappa = 0.71). Related to the right side, it was found to be kappa = 0.47 and kappa = 0.62, respectively to A and B. The intraexaminer agreement for the detection of MF was good for both examiners interpreting the left side (A: kappa = 0.61; B: kappa = 0.63), and in relation to the right side, it was moderate (A: kappa = 0.51) and fair (B: kappa = 0.38). The intraexaminer agreement in the detection of MCR was good and from good to fair in the detection of MF.
Keywords: radiography; panoramic; mandible; mandibular nerve; reproducibility of results